Impact of newly introduced perennial bioenergy crops on soil quality parameters at three different locations in W‐Germany. Issue 6 (23rd October 2017) - Emmerling, Christoph; Schmidt, Axel; Ruf, Thorsten; von Francken-Welz, Herbert; Thielen, Sebastian
Abstract: The land areas used for bioenergy crop cultivation are increasing across Europe. For several years now, various perennial crops have been cultivated, including Miscanthus, switchgrass and reed canary grass, and the newly introduced cup plant, giant knotweed, tall wheatgrass, virginia mallow, and wild plant mixtures. We investigated the impact that many of these perennial bioenergy crops (PECs) have on the soil organic C and N pools, microbial properties, and earthworm activity at three different study sites in W‐Germany with varying soil conditions after an experimental period of five years. Silage maize ( Zea maize ) in rotation with green rye ( Cecale cereale ) or Triticale was used for comparison (= annual energy crops; AEC). The overall intention of this study was to gain insights into the future trends of soil quality with changes in land‐use towards bioenergy production. Our results emphasized that in general, soil quality was improved through the cultivation of perennials. For example, after five years of investigation, the mean soil organic carbon contents increased, on average, by 1–2% at two of the three study sites, the soil microbial biomass increased from 13% (virginia mallow) to 27% (tall wheatgrass) ( p < 0.05) compared to AEC treatment and the mean earthworm activity (cast production) was significantly improved in PECs compared to AEC. These trends were mainly found in silty to loamy soils, but the results were slightly different in sandy soils and dry climate conditions. We suggest that this might be traced back to unfavourable growing conditions for perennial crops during the first years of establishment. To our knowledge, this is the first comprehensive field investigation of the impact of these newly introduced perennial crops on soil quality indicators that considers various site‐ and soil‐specific growth conditions.